Fetus in fetu in a 1-year-old female: A case report - Ayushi Agarwal; Meetu Agrawal; Sana Ahuja (Elsevier, 2024)
Background: Fetus in fetu (FIF) is an exceedingly rare congenital anomaly characterized by the presence of a partially developed fetus within the body of its twin. It is a rare entity with fewer than 200 cases documented worldwide. Typically presenting as an abdominal mass in early childhood, this condition remains a diagnostic challenge due to its infrequency and varied clinical manifestations. Case presentation: We present the case of a 1-year-old female child referred to the pediatric surgery department due to an abdominal mass detected by her parents. Physical examination revealed a firm, ill-defined mass in the right upper abdomen. Ultrasonography delineated a heterogeneous, calcified mass in the right upper quadrant. Laboratory investigations (complete blood count, viral markers), including tumor markers (AFP, beta-hCG), were within normal limits.A midline laparotomy was performed, and intraoperative findings revealed a well-encapsulated mass adherent to the retroperitoneum, adjacent to the liver. Careful dissection was carried out to preserve vital structures, and the mass was successfully removed without rupture. Histopathological examination confirmed the diagnosis of fetus in fetu, displaying a spectrum of tissues reminiscent of embryonic development, including skin, adnexal structures, brain tissue, mature cartilage, adipose tissue, bone marrow elements, and a partially developed vertebral column. After the surgical resection, the patient experienced an uneventful postoperative recovery. At one year of follow up the patient has shown no signs of recurrence. Conclusion: FIF is characterized by diagnostic challenges, often requiring postoperative histological confirmation. Histopathological examination confirmed the presence of FIF. Surgical excision, is crucial for favorable outcomes, especially in preventing potential complications. Comprehensive histopathological evaluation remains imperative for accurate diagnosis.